Dr. Jamil Jalibi and Pakistani Culture - Ghulam Abbas (بازیافت, 2017)
Dr Jamil Jalibi is a renouned scholar and great researcher . He has been busy in his literary, critical and scholarly work for the last seven decades. Cultural issues remained a ponit of focus in his criticism. According to him, Islam is centra force and cultural history and Urdu language are also basic ingredients of pakistani culture. We got Pakistan to promote our culture without fear and pressure but unfortunately we were trapped in the idea of superiority of loacal cultures over national cultue. We ingnored basic rules of social justice that produced frustration among different groups. The only solution of these problems is revival of fundamental idealogy , unity of ideas about national culture and creative endevour to reunite the nation.